Water insecurity in the Global North: A review of experiences in U.S. colonias communities along the Mexico border. (27th April 2022) - Wutich, Amber; Jepson, Wendy; Velasco, Carmen; Roque, Anais; Gu, Zhining; Hanemann, Michael; Hossain, Mohammed Jobayer; Landes, Laura; Larson, Rhett; Li, Wen Wen; Morales, Olga; Patwoary, Nargish; et al.
Abstract: Since the late 1970s, the term "colonias" (in English) has described low‐income, peri‐urban, and rural subdivisions north of the U.S.‐Mexico border. These communities are in arid and semi‐arid regions—now in a megadrought—and tend to have limited basic infrastructure, including community water service and sanitation. Recent scholarship has demonstrated how colonias residents experience unjust and inequitable dynamics that produce water insecurity in the Global North. In this review, we explain why U.S. colonias are an important example for theorizing water insecurity in the United States and beyond in the Global North. Tracing the history of water infrastructure development in U.S. colonias, we show how colonias are legally and socially defined by water insecurity. We draw on the published literature to discuss key factors that produce water insecurity in U.S. colonias: political exclusion, municipal underbounding, and failures in water quality monitoring. We show that water insecurity had led to negative outcomes—including poor water access, risks to physical health, and mental ill‐health—in U.S. colonias. We present four possible approaches to improving water security in U.S. colonias: (1) soft paths & social infrastructure for water delivery, (2) decentralized water treatment approaches, such as point‐of‐use, point‐of‐entry, and fit‐for‐purpose systems; (3) informality, including infrastructural, economic, and socio‐cultural innovations; and (4) political, policy, and law innovations and reforms. At the same time, we reflect seriously on how water security can be ethically achieved in partnership and aligning with the visions of U.S. colonias residents themselves. This article is categorized under: Human Water > Water Governance Engineering Water > Water, Health, and Sanitation Abstract : A model for understanding the causes, consequences, and solutions for water insecurity in colonias north of the U.S.‐Mexico border